An enhanced Forensic-Based Investigation algorithm and its application to optimal design of frequency-constrained dome structures. (November 2021) - Kaveh, Ali; Hamedani, Kiarash Biabani; Kamalinejad, Mohammad
Highlights: An Enhanced Forensic-Based Investigation (EFBI) algorithm is proposed. EFBI aims to improve the balance between intensification and diversification in FBI. Comparison is made for three well-studied dome-like truss optimization problems. This is the first time that FBI is applied to structural optimization. It is shown that EFBI significantly outperforms the standard FBI. Abstract: In this paper, an Enhanced Forensic-Based Investigation (EFBI) is proposed for optimal design of frequency-constrained dome-like trusses. The Forensic-Based Investigation (FBI) algorithm is a newly developed population-based metaheuristic inspired by the criminal investigation process. Throughout the FBI algorithm, the investigation and pursuit teams (i.e., the diversification and the intensification components of FBI, respectively) cooperate with each other to solve the target optimization problem. This study aims to modify the original formulation of FBI and propose an enhanced version of FBI, named as EFBI. The proposed EFBI seeks to reinforce communication between the investigation and pursuit teams with the aim of striking a better balance between the intensification and the diversification tasks. The performance of the proposed EFBI is compared with those of the standard FBI and some other optimization methods through three well-studied dome truss optimization problems with frequency constraints. To the best of our knowledge, this is the first time that FBI is applied to structural optimization. Results confirm that EFBI significantly outperforms the standard FBI, and has superior or comparable performance to other considered metaheuristics.